Um processo multimétodo de foresight organizacional baseado em práticas reflexivas individuais e grupais sobre modelos mentais - Bernardo de Castro Silva Menegale (2022)
Studies about the Future have been being embedded to corporate strategy development and planning since the 1950s, when the scenario-planning practices were disseminated within corporate environment. Through the study of the Future, specially through foresight, organizations became more capable to identify and seize opportunities, acting more in advance. However, despite of the evolution of studies of the Future and Corporate Strategy, little emphasis is given to the strategist role. He/she is the one responsible for interpreting environment factors, analyzing scenarios and making decision regarding corporate strategy and pointing paths to be followed. In that regard, the field of Behavioral Strategy advocates that strategists are biased, and have individual characteristics and, through them, create their mental models, interpretate scenarios and make decisions. In other words, individual factors shape corporate strategy as they impact strategists’ decision policies. Thus, organizations that have a participative strategic-planning process, involving different strategists, show different decision policies over the same question. Reaching alignment throughout the professionals involved become more complex as decision policies are implicit, that is, are neither clear nor evident. Thus, organizations are able to reach alignment through the identification and elucidation of individual factors that impact decision policies, stimulating the explication of differences and the debate around the different perspectives to reach strategy alignment. Therefore, this research purposes a process for organizational foresight based on the cognitive models of strategists from a Technology Center: an organization embedded in a context of high uncertainty and which the strategic decision-making process is integrative. The model relies on the identification, elucidation and understanding of the individual factors that impact strategists’ decision policies. For this, several methods and techniques were combined in a sequential process, structured in four phases: Strategic-questions definition, Scenario and Paths definition, Policy-capturing, and Validation. Finally, this research delivers a tested and tunned model able to be replicated to different organizations in similar contexts, generating purposeful knowledge of a strategic decision-making process that considers and aggregates different strategists and their points of view.